Dampak Orientasi Pasar Hijau dan Inovasi Hijau Terhadap Kinerja Bisnis UMKM Kawasan Pariwisata Taman Mini Indonesia Indah - Arif Nugroho; Erny Novianti; Widya Lelisa Army (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Tourism is an activity / trip that a person does with a temporary time, a planned schedule and has a destination to a place and has certain motives but not to find work and livelihood in the destination area. This study uses a quantitative method, which uses two independent variables, namely stakeholders and green innovation and one dependent variable, namely business performance. This study aims to determine how much influence green market orientation has on business performance, and the influence of green innovation on business performance. The data used in this study are primary data and secondary data, obtained from the field and library data. The sample in this study were 30 medium-sized businesses or MSMEs, the results of this study indicate that green market orientation and green innovation are very influential on umkm business performance, based on research results of around 91%, because the pressure of green market orientation emphasizes more business actors or companies to be more environmentally friendly as a result of company activities that affect the environment, while green innovation affects market share with processes and various environmentally friendly products.